"Like a cow that gave birth to a seagull": Amos Oz, Yoel Hoffmann and the birth of The Same Sea. Issue 2 (2nd July 2020) - Stahl, Neta
ABSTRACT: This article examines Oz's novel The Same Sea (1999) and argues that it marks the novelist's attempt to join a new phase in Israeli literature. Comparing The Same Sea to two novels by Yoel Hoffmann, one of the most famous representatives of this phase, the article sheds light on Oz's struggle to balance between the writing norms that helped establish his status as "the shaman of the tribe" and the new norms, associated with Israeli postmodernism.